A Landscape Analysis of Offering HIV Testing Services Within Family Planning Service Delivery - Drake, Alison L.; Quinn, Caitlin; Kidula, Nancy; Sibanda, Euphemia; Steyn, Petrus; Barr-DiChiara, Magdalena; Jamil, Muhammad S.; Rodolph, Michelle; Gaffield, Mary E.; Kiarie, James; Baggaley, Rachel; Johnson, Cheryl (Frontiers in Reproductive Health, 2021)
Introduction: Offering HIV testing services (HTS) within sexual and reproductive health (SRH) services is a priority, especially for women who are at substantial HIV risk. To reach women with HIV who do not know their status and prevent mother-to-child HIV transmission, World Health Organization (WHO) recommends routinely offering HTS as part of family planning (FP) service delivery in high HIV burden settings. We conducted a landscape analysis to assess HTS uptake and HIV positivity in the context of FP/SRH services. Assessment of policy options: We searched records from PubMed, 4 grey literature databases, 13 organization websites, and emailed 24 organizations for data on HTS in FP/SRH services. We also obtained data from International Planned Parenthood Federation (IPPF) affiliates in Eswatini, Kenya, Lesotho, Malawi, Namibia, Uganda, Zambia, and Zimbabwe. Unique programs/studies from records were included if they provided data on, or barriers/facilitators to, offering HTS in FP/SRH. Overall, 2,197 records were screened and 12 unique programs/studies were eligible, including 10 from sub-Saharan Africa. Four reported on co-delivery of SRH services (including FP), with reported HTS uptake between 17-94%. Six reported data on HTS in FP services: 4 among general FP clients; 1 among couples; and 1 among female sex workers, adolescent girls, and young women. Two of the 6 reported HTS uptake >50% (51%, 419/814 Kenya; 63%, 5930/9439 Uganda), with positivity rates of 2% and 4.1%, respectively. Uptake was low (8%, 74/969 Kenya) in the one FP program offering pre-exposure prophylaxis. In the IPPF program, seven countries reported HTS uptake in FP services and ranged from 4% in Eswatini to 90% in Lesotho; between 0.6% (Uganda) and 8% (Eswatini) of those tested were HIV positive. Implications: Data on providing HTS in FP/SRH service delivery were sparse and HTS uptake varied widely across programs. Actionable recommendations: As countries expand HTS in FP/SRH appropriate to epidemiology, they should ensure data are reported and monitored for progress and impact.